Semantic Perspective on Lexical Ambiguity in English Tetxbook - Wiyanto, Muhammad Saibani (English Education:Journal of English Teaching and Research, 2022)
The goal of this study is to describe the many types of lexical ambiguity and how they are used in student English textbooks. Ullman Stephen proposed the linguistic ambiguity theory. The essay combined qualitative research with a content analysis technique. The words with lexical ambiguity are the subjects of this study. The data is made up of words, and the source is an English textbook. Reading, comprehending, and coding the text book that contains lexical ambiguity is the procedure for gathering data. The data analysis technique is then organized, familiarized, and interpreted. The findings of the study revealed that the text book contained two types of lexical ambiguity, Polisemy and Homonymy. Lexical Ambiguity can be assumed to exist in everyword with several meanings. Keywords: semantic; lexical ambiguity; textbook